Altered Morphological Characteristics Associated With Spatial Working Memory Performance in Children With ADHD - Lanfang Chen; Yishan Lin; Qianhui Wang; Chao Zhang; Shuqin Zhang; Rui Li; Lili Lin; Qianqian Sun; Yi Zeng (Journal of Integrative Neuroscience)
Background: Spatial working memory (SWM) deficit is a common problem in attention deficit disorder with hyperactivity (ADHD), often correlating with the severity of ADHD symptoms and academic difficulties. Although previous studies have broadly described abnormal brain structural changes in ADHD, the potential changes in brain morphology in children with ADHD with SWM dysfunction are still uncharacterized. This cross-sectional study was used to elucidate the brain morphological alterations associated with SWM performance in boys with ADHD. Methods: Data for this investigation were retrieved from one public dataset. A cohort of 23 boys diagnosed with ADHD and an age-matched group of 23 healthy male controls were selected for the study. Participants were administered n-back SWM tasks, with task accuracy and response times recorded. Voxel-based morphometry (VBM) was used to quantify gray matter (GM) volume, thereby characterizing the brain morphological features in both the ADHD and healthy control groups. Linear or rank correlation analyses were conducted to examine the relationship between GM volume and SWM task performance. Results: VBM analysis revealed significantly lower GM volume in the right middle cingulate cortex (MCC), left precuneus, and right retrosubicular region among boys with ADHD. Moreover, a significant positive correlation was observed between the GM volume of the right MCC and the accuracy of the 2-back SWM task under conditions of small reward and immediate feedback. Conclusion: The reduced GM volume in the right MCC, left precuneus, and right retrosubicular might have a potential impact on SWM performance in children with ADHD.